A randomized, double-blind sham-controlled trial on the efficacy of arthroscopic tennis elbow release for the management of chronic lateral epicondylitis. Issue 1 (December 2016) - Matache, Bogdan; Berdusco, Randa; Momoli, Franco; Lapner, Peter; Pollock, J.
Abstract Background Tennis elbow is a common elbow pathology typically affecting middle-aged individuals that can lead to significant disability. Most cases resolve within 2 years of symptom onset, but a subset of patients will develop persistent symptoms despite appropriate conservative management. There are several surgical approaches used to treat chronic tennis elbow, with arthroscopic surgery becoming an increasingly popular approach to address this pathology in North America. This procedure involves the arthroscopic release of the extensor carpi radialis brevis tendon (ECRB) origin at the elbow. The potential benefit of arthroscopic treatment of this condition is improved patient outcomes and shorter recovery time following surgery. The results of this technique have been reported only in the context of case series, which have shown positive results. However, in order to justify its widespread use and growing popularity, a high level of evidence study is required. The purpose of this prospective, randomized sham-controlled trial is to determine whether arthroscopic tennis elbow release is effective at treating chronic lateral epicondylitis. Methods We will conduct a prospective single center, double-blind, randomized sham-controlled parallel arm trial evaluating the efficacy of arthroscopic tennis elbow release in adult patients with symptoms for at least 6 months. Patients will undergo intraoperative randomization after diagnostic arthroscopy of the elbow to receive either ECRB release (through the creation of a lateral portal) or a sham lateral portal and no ECRB release. The primary outcome will be the Mayo Elbow Performance Score (MEPS) at 1 year follow-up. Secondary outcomes will be the abbreviated Disability of the Shoulder and Hand (DASH) score, American Shoulder and Elbow Surgeons elbow (ASES-e) score and grip strength at 3, 6, 12 and 24 months as well as return-to-work time, ability to return to full duty and adverse outcomes. Discussion Results of this study will provide empirical high quality evidence to guide clinical decision-making in patients with chronic tennis elbow. Trial registration NCT02236689 (September 8, 2014)